RADIOTHERAPY TECHNIQUE INTENSITY MODULATED RADIATION THERAPY (IMRT) IN BREAST CANCER CASES IN PASAR MINGGU HOSPITAL - Dody Arland; Nursama Heru; Khairil Anwar; Petra P Wellyam; Dea Ryangga; Danil Hulmansyah (LPPM Universitas Awal Bros, 2025)
Background: Breast cancer is the most common type of cancer among women in Indonesia and remains one of the leading causes of cancer-related mortality. Radiotherapy plays a crucial role as both an adjuvant and curative treatment modality to improve local disease control following surgery. Advances in radiotherapy technology have led to the development of Intensity Modulated Radiation Therapy (IMRT), which enables highly conformal dose distribution to the target volume while minimizing radiation exposure to surrounding healthy tissues. Nevertheless, the clinical implementation of IMRT for breast cancer treatment in hospitals still requires evaluation of the treatment workflow and irradiation techniques to ensure optimal therapeutic outcomes.This study aimed to describe the implementation of the IMRT technique in breast cancer patients at the Radiotherapy Installation of Pasar Minggu Regional General Hospital, from the initial consultation to the completion of radiotherapy treatment. Methods: This study employed a qualitative approach using a case study design involving a breast cancer patient. Data were collected through direct observation of the radiotherapy workflow, including consultation with a radiation oncologist, CT simulation, Treatment Planning System (TPS), verification using an On-Board Imager (OBI), and radiation delivery using a Linear Accelerator (LINAC). Results: Radiotherapy planning was performed using the IMRT technique with six irradiation fields at gantry angles of 20°, 60°, 220°, 260°, 300°, and 340°. Evaluation of the Dose Volume Histogram (DVH) demonstrated that target dose coverage remained within the International Commission on Radiation Units and Measurements (ICRU) recommended range of 95–107%. Patient positioning verification using anterior–posterior/posterior–anterior (AP/PA) and lateral OBI imaging confirmed accurate patient alignment prior to treatment. The prescribed radiation dose was 5000 cGy delivered in 25 fractions of 200 cGy each.